Pembersihan dan Sosialisasi Program Penghijauan 3R (Reduce, Reuse, Recycle) - Jesslyn, Felby; Morris, Morris; Putri, Nurul Syafira; Lim, Hendra Wijaya; Efendi, Efendi; Sianipar, David Bonardo; Hudori, Mahfuz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The purpose of this study was to determine whether the community around the Ma'dare coast knowing about beach cleaning and socialization of the 3R (Reduce, Reuse, Recycle) program location in Kampung Melayu RT 01 RW 08 Batu Besar, Nongsa. From the survey results, we found that with a population of approximately 2,600 people, people are categorized as capable. Because the performance of the Kampung Melayu settlement includes people who have an advanced mindset to prosper the community by promoting the beauty of the beach there named Ma'dare beach. Our goal is to carry out this cleansing and outreach program to provide an understanding of the importance of separation between organic and non-organic waste to the people of RW 08 and visitors there. Data collection instruments use documentation via mobile phones or gadgets. Security via gadget is very helpful for us to document the real case like we can take a picture of how it is there, make a video which contain of Kampung Melayu citizen and ask them about the existing circulation system and public awareness of the reforestation.